1996
DOI: 10.1111/j.1398-9995.1996.tb00057.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of benzyl benzoate and different chemicals as acaricides

Abstract: Several observations have indicated that house‐dust mites (HDM) play an important role in allergic diseases. Thus, the primary form of treatment should aim at reducing exposure to HDM for these patients. Allergenavoidance measures in homes have been demonstrated to be beneficial in decreasing the risk of sensitization, severity of symptoms, bronchial reactivity, and basophil sensitivity. Various chemical methods, as well as physical measures, have been tried to eliminate mite allergens from house dust. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…The mortality rate of the mites was assessed after 24 h, following previous testing of acaricidal activity in HDM (Kalpaklioglu et al 1996). The lowest concentration of each acaricide that caused 100% mortality was chosen for further acaricidal activity study: groups of 20 adult mites were continuously exposed to 500 mg/m 2 permethrin, 900 mg/m 2 deltamethrin, 5000 mg/m 2 lamdacyhalothrin, 1250 mg/m 2 esbioallenthrin, 40000 mg/m 2 bifenthrin, or 312.5 mg/m 2 benzyl benzoate.…”
Section: Acaricidal Activity Of Six Compounds and Test Set-up Effectimentioning
confidence: 99%
“…The mortality rate of the mites was assessed after 24 h, following previous testing of acaricidal activity in HDM (Kalpaklioglu et al 1996). The lowest concentration of each acaricide that caused 100% mortality was chosen for further acaricidal activity study: groups of 20 adult mites were continuously exposed to 500 mg/m 2 permethrin, 900 mg/m 2 deltamethrin, 5000 mg/m 2 lamdacyhalothrin, 1250 mg/m 2 esbioallenthrin, 40000 mg/m 2 bifenthrin, or 312.5 mg/m 2 benzyl benzoate.…”
Section: Acaricidal Activity Of Six Compounds and Test Set-up Effectimentioning
confidence: 99%
“…(8,37,42,43) Vacuuming alone or in combination with very hot water has been found to be effective at killing mites and removing allergens, (9) but some investigators have found that vacuuming removes dust mites' natural predators, cheyletus mites, (44) which produces more dust mites. (45,46) Two studies have examined the impact of steam cleaning on allergen removal from carpet.…”
Section: Inactivation Of Dust Mites Dust Mite Allergen and Mold Fromentioning
confidence: 98%
“…Mitigation techniques to control dust mite and dust mite allergens consist of either physical methods, such as vacuuming or steam cleaning, or chemical treatment with acaricides, such as benzyl benzoate, (29,(37)(38)(39) disodium octaborate tetrahydrate, (40,41) and tannic acid. (8,37,42,43) Vacuuming alone or in combination with very hot water has been found to be effective at killing mites and removing allergens, (9) but some investigators have found that vacuuming removes dust mites' natural predators, cheyletus mites, (44) which produces more dust mites.…”
Section: Inactivation Of Dust Mites Dust Mite Allergen and Mold Fromentioning
confidence: 99%
“…This dictum was largely based on a positive association observed between high levels of mite allergen exposure and the manifestation of asthma (Sporik et al 1990), bronchial hyperresponsiveness (Custovic et al 1996), and IgE-mediated sensitization in young children (Torrent et al 2006), although recent studies have suggested the existence of a complex, non-linear relationship (Schram-Bijkerk et al 2006;Tovey et al 2008). Such control measures as encasing mattresses/pillows with impermeable covers (Mahakittikun et al 2006), washing bedding in hot water ([55°C) (McDonald and Tovey 1992), exposing loose carpets to direct sunlight (Tovey and Woolcock 1994), vacuuming (Adilah et al 1997), using acaricides (Kalpakhoglu et al 1996) which kill upon contact, or replacing carpets with vinyl or wooden floors (Tovey and Marks 1999) have been recommended. While the efficacy of these control measures has been challenged (Custovic and van Wijk 2005), Colloff (2009) has cited 12 trials/studies showing significant clinical improvement over the control group in asthma-related outcome measures.…”
Section: Introductionmentioning
confidence: 98%